A high coercivity NdFeB magnetic material and preparation method thereof

By attaching heavy rare earth layers and light rare earth layers on both sides of the magnetic body of the NdFeB magnetic material, a high magnetic hardening layer is formed by diffusion and replacement of heavy rare earth elements, the problem of high coercive force enhancement cost in the prior art is solved, and the effect of high coercive force and low cost is achieved.

CN115101281BActive Publication Date: 2025-03-07NINGBO HELI MAGNET TECH CO LTD

Patent Information

Application Number
CN202210922137.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-02
Publication Date
2025-03-07
Estimated Expiration
2042-08-02

AI Technical Summary

Technical Problem

When existing NdFeB magnetic materials increase coercive force, the cost is high and the addition of heavy rare earth elements will affect the residual magnetism.

Method used

By attaching heavy rare earth layers and light rare earth layers on both sides of the magnetic material body, a high magnetic hardening layer is formed by diffusion and displacement of heavy rare earth elements, reducing the exchange and coupling between the main phase grains, thereby improving coercivity, and reducing costs by optimizing the thickness of the light rare earth layers and heavy rare earth layers.

Benefits of technology

It is achieved to significantly increase the coercive force of NdFeB magnetic materials at a lower dysprosium addition amount, while reducing the preparation cost of magnetic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003778192430000071
    Figure BDA0003778192430000071
Patent Text Reader

Abstract

The present application relates to the field of magnet technology, and specifically discloses a high coercive force NdFeB magnetic material and a preparation method thereof. The high coercive force NdFeB magnetic material of the present application includes a magnetic material body, a heavy rare earth layer and a light rare earth layer. The magnetic material body is mainly made of the following raw materials: neodymium, gadolinium, copper, boron, cerium, aluminum, niobium iron, and iron; the preparation method includes: the preparation of the magnetic material body includes the following steps: melt stripping, hydrogen crushing and grinding, pressing and molding, and sintering to obtain a magnetic material body one; the preparation of the heavy rare earth layer includes the following steps: slicing, mixing, heating and melting, evaporation, and forming a thin film on one side of the slice; infiltration, quenching and tempering treatment to obtain a magnetic material body two; the preparation of the light rare earth layer includes the following steps: preparing a light rare earth alloy sheet, the light rare earth alloy sheet is attached to the side of the magnetic material body two opposite to the heavy rare earth layer, and thermal diffusion and tempering are performed to obtain the magnetic material body two. The NdFeB magnetic material of the present application has high coercive force and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of NdFeB magnet preparation, and more specifically, to a high coercive force NdFeB magnetic material and a preparation method thereof. Background Art

[0002] Rare earths are globally recognized as key strategic resources and are hailed as "vitamins of modern industry" and "treasure trove of new materials in the 21st century". Neodymium iron boron is the third-generation rare earth permanent magnet with the best comprehensive quality to date. It is widely used due to its high performance, energy saving and environmental protection, rich reserves of raw material resources, mature processing technology and low cost.

[0003] NdFeB magnets are currently the most magnetic permanent magnet materials. Their main raw materials are rare earth metal neodymium, metallic element iron, non-metallic element boron, and a small amount of added dysprosium and other elements. They have the characteristics of high remanence, high coercive force, and high magnetic energy product.

[0004] In order to increase the coercivity of NdFeB permanent magnets, dysprosium and terbium are usually added to improve anisotropy. However, since the atomic magnetic moments of heavy rare earth and iron are antiferromagnetically coupled, the addition of these elements will affect the remanence and increase the cost of NdFeB magnets. Summary of the invention

[0005] In order to further improve the coercivity of NdFeB magnetic materials while reducing the preparation cost of NdFeB magnetic materials, the present application provides a high coercivity NdFeB magnetic material and a preparation method thereof.

[0006] In the first aspect, the present application provides a high coercive force NdFeB magnetic material, which adopts the following technical solution: a high coercive force NdFeB magnetic material, comprising a magnetic material body and a coating attached to the surface of the magnetic material body, wherein the coating comprises a heavy rare earth layer located on the surface of the magnetic material body and a light rare earth layer located on the opposite side of the magnetic material body, wherein the magnetic material body is mainly made of the following raw materials in parts by weight: 70-80 parts of neodymium, 30-40 parts of gadolinium, and 0.5-1 parts of copper. , 30-35 parts of boron, 90-100 parts of cerium, 2-3 parts of aluminum, 1-5 parts of ferroniobium, and 350-370 parts of iron. The heavy rare earth slurry of the heavy rare earth layer is mainly made of the following raw materials in parts by weight: 5-10 parts of dysprosium trifluoride, 2-3 parts of dysprosium nitride, 2-3 parts of dysprosium-nickel alloy, and 2-3 parts of iron; the light rare earth slurry of the light rare earth layer is mainly made of the following raw materials in parts by weight: 5-8 parts of copper-niobium alloy and 3-5 parts of praseodymium-copper alloy.

[0007] By adopting the above technical scheme, the heavy rare earth layer and the light rare earth layer are distributed on both sides of the magnetic material body along the thickness direction. The NdFeB magnet prepared in this application is a rectangular block. The enrichment of dysprosium in the heavy rare earth layer at the interface between the matrix phase and the grain boundary phase and close to the matrix phase is beneficial to greatly increase the coercive force of the magnetic material body at a lower dysprosium addition amount. At the same time, the fluorine element is dissolved in the neodymium-rich grain boundary phase, reducing the thickness of the area with a smaller anisotropy field. Nitrogen and nickel can also be used as diffusion media to improve the coercive force of the magnetic material body. Dysprosium diffuses along the grain boundary and replaces the magnetic field at the grain boundary. The neodymium atoms in the material form a magnetic hardening layer with a high anisotropy field, which inhibits the nucleation of the reverse magnetization domain, thereby improving the coercive force of the magnetic material. The heavy rare earth elements of the present application are only enriched in the surface layer of the grains and will not enter the magnetic material in large quantities, thereby reducing the amount of heavy rare earth elements and improving the coercive force of the magnetic material. The attachment of the light rare earth layer is based on the light rare earth as the raw material and diffuses into the magnetic material through the grain boundary, with the grain boundary phase of the magnetic material as the diffusion channel. By increasing the non-magnetic grain boundary phase, the exchange coupling between the main phase grains is reduced, thereby improving the coercive force of the magnetic material.

[0008] Preferably, the magnetic material body also includes 2-3 parts of titanium and 1-2 parts of carbon.

[0009] By adopting the above technical scheme, titanium and carbon are added to the magnetic material body. The solubility of titanium in the NdFeB phase is relatively low. During the grain growth process, the titanium element gathers at the grain boundaries of the NdFeB magnet to inhibit grain growth. The titanium element and the carbon element cooperate with each other to form titanium carbide at the grain boundaries, thereby further inhibiting grain growth. Titanium carbide has the function of isolating hard magnetic phase grains, which is convenient for improving the coercive force of the magnetic material body.

[0010] Preferably, the ratio of the thickness of the heavy rare earth layer to the thickness of the magnetic material body is (1-2):(5-6).

[0011] By adopting the above technical solution, the thickness of the heavy rare earth layer of the present application is relatively small, which is convenient for the heavy rare earth elements in the heavy rare earth layer to diffuse into the magnetic material body on the basis of satisfying the crystal plane regulation, thereby improving the coercive force of the magnetic material body. The greater the thickness, the more heavy metal is added, and part of the heavy metal is not diffused into the magnetic material matrix, resulting in a waste of heavy metals, and at the same time, the preparation cost of the magnetic material is increased.

[0012] Preferably, the ratio of the thickness of the light rare earth layer to the thickness of the magnetic material body is (4-6):(5-6).

[0013] By adopting the above technical solution, the thickness of the light rare earth layer is adjusted, thereby significantly reducing the exchange coupling between the main phase grains, thereby increasing the coercive force of the magnetic material body. The cost of the raw materials used in the light rare earth layer is relatively low, thereby reducing the preparation cost of the magnetic material on the basis of increasing the coercive force of the magnetic material body.

[0014] In a second aspect, the present application provides a method for preparing a high coercive force NdFeB magnetic material, using the following technical solution:

[0015] A method for preparing a high coercivity NdFeB magnetic material, comprising:

[0016] (1) Preparation of magnetic material body, including the following steps: S1, melting and stripping: the above raw materials are melted and stripped to obtain stripped sheets; S2, hydrogen crushing and grinding: the stripped sheets obtained in step S1 are subjected to hydrogen crushing and air flow grinding to obtain hydrogen crushing powder; S3, pressing and molding: the hydrogen crushing powder obtained in step S2 is pressed and shaped and oriented to obtain a raw magnet; S4, magnetic material body: the raw magnet in step S3 is sintered to obtain a magnetic material body 1;

[0017] (2) Preparation of a heavy rare earth layer, comprising the following steps: A1, slicing: slicing the magnetic material body obtained in step (1) into thin slices; A2, mixing: mixing dysprosium trifluoride, dysprosium nitride, and dysprosium-nickel alloy to form a mixed powder, heating the mixed powder to melt and evaporate, and forming a thin film on one side of the slice obtained in step A1 to obtain a thin film slice; A3, infiltration treatment: performing infiltration treatment on the thin film slice obtained in step A2 to obtain a treated thin slice; A4, heat treatment: performing quenching and tempering treatment on the treated thin slice obtained in step A3 to obtain a second magnetic material body;

[0018] (3) Preparation of a light rare earth layer, comprising the following steps: B1, preparation of a light rare earth alloy sheet: using a rapid solidification process to melt the raw materials and pour them onto a copper roller to obtain a cast sheet, namely, a light rare earth alloy sheet; B2, preparation of a NdFeB magnet: attaching the light rare earth alloy sheet obtained in step B1 to the side of the second magnetic body opposite to the heavy rare earth layer, performing thermal diffusion treatment and tempering treatment, thereby obtaining the magnet.

[0019] Preferably, the size after slicing in step A1 is (6-8) mm×(6-8) mm×(5-7) mm.

[0020] Preferably, the casting in step B1 is cut into a size similar to that of the slices in step A1.

[0021] By adopting the above-mentioned technical scheme, the present application attaches a heavy rare earth layer and a light rare earth layer on two opposite sides of the magnetic material body, diffuses the heavy rare earth elements in the heavy rare earth layer, replaces the neodymium atoms in the magnetic material at the grain boundaries, and forms a magnetic hardening layer with a high anisotropy field, thereby improving the coercive force of the magnet. The attachment of the light rare earth layer facilitates the diffusion of the light rare earth raw material into the magnetic material body, reduces the exchange coupling between the main phase grains, and at the same time, reduces the preparation cost of the magnetic material while improving the coercive force of the magnetic material.

[0022] Preferably, between the slicing in step A1 and the mixing in step A2, the slices are pretreated and dried for later use, and the pretreatment is any one of alcohol wiping, electrostatic dust removal, and ultrasonic cleaning.

[0023] By adopting the above technical scheme, the slices are pre-treated to facilitate cleaning of dust or oil on the surface of the slices, thereby increasing the adsorption strength of the heavy rare earth layer and the light rare earth layer on the surface of the slices, thereby increasing the diffusion effect of the heavy rare earth in the heavy rare earth layer within the slices and the diffusion effect of the light rare earth in the light rare earth layer within the slices.

[0024] Preferably, the particle size of the hydrogen-fragmented powder in step S2 is 2-8 μm.

[0025] By adopting the above technical scheme, grain refinement makes the grain boundaries evenly and densely distributed, and the crack propagation path is changed, which is convenient for improving the coercive force of the magnet. At the same time, it is convenient to reduce the amount of expensive heavy rare earth added to the magnet and reduce costs. At the same time, the neodymium-rich phase in the magnet made of small-sized grains is evenly distributed; the grains are small and uniform, which is convenient for improving the coercive force. According to the pinning field theory of coercive force, there is no abnormally large-sized agglomeration of the neodymium-rich phase, so that the microstructure of the magnet is evenly distributed, thereby improving the coercive force of the magnet.

[0026] Preferably, the density of the raw magnet in step S3 is 2-5 g / cm 3 .

[0027] By adopting the above technical scheme, the present application optimizes the density of the raw magnet, thereby improving the diffusion of heavy metals in the heavy rare earth layer and light metals in the light rare earth layer into the magnetic material body, thereby improving the coercive force of the magnetic material body. If the density of the raw magnet is too large, the heavy rare earth and light rare earth are difficult to diffuse to the middle of the raw magnet. If the density is too small, the efficiency of heavy rare earth and light rare earth replacing neodymium atoms is low. The density of the raw magnet of the present application is convenient for improving the efficiency of diffusion and replacement of heavy rare earth and light rare earth, thereby improving the coercive force of the magnetic material body.

[0028] Preferably, carbon particles are added to the mixture in step A2.

[0029] By adopting the above technical solution, carbon particles are used during the evaporation process to reduce the oxygen in the evaporation chamber and reduce the oxidation of the iron element, so that the iron element and other elements are evaporated to the surface of the thin film, and at the same time, the dysprosium element can flow smoothly in the grain boundary channel.

[0030] Preferably, the sintering temperature in step S4 changes in a gradient. After vacuuming, the temperature is increased to 750-850°C at a heating rate of 5-10°C / min, and kept warm for 20-40min; the temperature is increased to 1000-1050°C at a heating rate of 3-5°C / min, and kept warm for 10-30min; the temperature is increased to 1050-1100°C at a heating rate of 1-2min, and kept warm for 300-350min; the temperature is reduced to 900-1000°C at a cooling rate of 3-4°C / min, the temperature is reduced to 700-800°C at a cooling rate of 5-7°C / min; the temperature is reduced to 600-700°C at a cooling rate of 6-8°C / min, and the temperature is reduced to room temperature at a cooling rate of 10-15°C / min.

[0031] By adopting the above-mentioned technical scheme, the present application adopts a step-by-step temperature increase to pre-sinter the magnetic material body, so that the temperature gradient between the outside and the center of the magnetic material body becomes smaller. When the sintering temperature is reached, the central part of the magnetic material body compact quickly reaches the sintering temperature, thereby improving the density and magnetic properties of the magnetic material body. At the same time, a staged cooling method is adopted to reduce the temperature in the sintering chamber to room temperature, thereby reducing the impact of the sudden temperature drop on the magnetic properties of the magnetic material body.

[0032] In summary, this application has the following beneficial effects:

[0033] 1. The high coercive force NdFeB magnetic material of the present application is prepared by attaching a heavy rare earth layer and a light rare earth layer to two opposite sides of the magnetic material body. The heavy rare earth layer and the light rare earth layer are located on two sides at the same height. The heavy rare earth elements and the light rare earth elements will not overlap when they diffuse. The attachment of the light rare earth layer makes it easy to reduce the amount of heavy rare earth elements added, thereby reducing the preparation cost of the magnetic material and, at the same time, improving the coercive force of the magnetic material.

[0034] 2. The high coercivity NdFeB magnetic material of the present application improves the coercivity of the magnetic material while reducing the preparation cost of the magnetic material by optimizing the thickness of the light rare earth layer and the heavy rare earth layer.

[0035] 3. In the preparation method of the high coercive force NdFeB magnetic material of the present application, when preparing the magnetic material body, during the sintering process, the magnetic material is pre-sintered by adopting a step-by-step temperature increase and decrease method, thereby improving the density and magnetic properties of the magnetic material body, and further improving the density and magnetic properties of the magnetic material. DETAILED DESCRIPTION

[0036] The present application is further described in detail below in conjunction with embodiments.

[0037] The mass ratio of dysprosium to nickel in the dysprosium-nickel alloy of the present application is (70-90):(10-30). Further optionally, the mass ratio of dysprosium to nickel is 80:20.

[0038] The atomic ratio of copper to niobium in the copper-niobium alloy of the present application is (97-99.5):(0.5-3). Further optionally, the atomic ratio of copper to niobium is 97:3.

[0039] The atomic ratio of praseodymium to copper in the praseodymium-copper alloy of the present application is (60-70):(30-40). Further optionally, the atomic ratio of praseodymium to copper alloy is 68:32.

[0040] The particle size of the hydrogen-broken powder in step S2 of the present application is 2-8 μm. Optionally, the particle size of the hydrogen-broken powder in step S2 is 5 μm.

[0041] The density of the raw magnet in step S3 of the present application is 2-5 g / cm 3 Optionally, the density of the raw magnet in step S3 is 4 g / cm 3 .

[0042] Preparation example of magnetic material

[0043] Preparation Example 1

[0044] The magnetic material body of this preparation example is made of raw materials of the following weights: 70 kg of neodymium, 30 kg of gadolinium, 0.5 kg of copper, 30 kg of boron, 90 kg of cerium, 2 kg of aluminum, 1 kg of ferroniobium, and 350 kg of iron.

[0045] Preparation Example 2

[0046] The magnetic material body of this preparation example is made of raw materials of the following weights: 80 kg of neodymium, 40 kg of gadolinium, 1 kg of copper, 35 kg of boron, 100 kg of cerium, 3 kg of aluminum, 5 kg of ferroniobium, and 370 kg of iron.

[0047] Preparation Example 3

[0048] The magnetic material body of this preparation example is made of raw materials of the following weights: 74.4 kg of neodymium, 34.8 kg of gadolinium, 0.9 kg of copper, 32 kg of boron, 91.2 kg of cerium, 2.4 kg of aluminum, 3 kg of ferroniobium, and 361.3 kg of iron.

[0049] Preparation Example 4

[0050] The magnetic material body of this preparation example is made of raw materials of the following weights: 74.4 kg of neodymium, 34.8 kg of gadolinium, 0.9 kg of copper, 32 kg of boron, 91.2 kg of cerium, 2.4 kg of aluminum, 3 kg of ferroniobium, 361.3 kg of iron, and 2 kg of titanium.

[0051] Preparation Example 5

[0052] The magnetic material body of this preparation example is made of raw materials of the following weights: 74.4 kg of neodymium, 34.8 kg of gadolinium, 0.9 kg of copper, 32 kg of boron, 91.2 kg of cerium, 2.4 kg of aluminum, 3 kg of ferroniobium, 361.3 kg of iron, 2 kg of titanium, and 2 kg of carbon.

[0053] Preparation Example of Heavy Rare Earth Slurry

[0054] Preparation Example 6

[0055] The heavy rare earth slurry of this preparation example is made of the following raw materials by weight: 5 kg of dysprosium trifluoride, 2 kg of dysprosium nitride, 2 kg of dysprosium-nickel alloy, and 2 kg of iron.

[0056] Preparation Example 7

[0057] The heavy rare earth slurry of this preparation example is made of the following raw materials by weight: 10 kg of dysprosium trifluoride, 3 kg of dysprosium nitride, 3 kg of dysprosium-nickel alloy, and 3 kg of iron.

[0058] Preparation example of light rare earth slurry

[0059] Preparation Example 8

[0060] The light rare earth slurry of this preparation example is made of the following raw materials by weight: 5 kg of copper-niobium alloy and 3 kg of praseodymium-copper alloy.

[0061] Preparation Example 9

[0062] The light rare earth slurry of this preparation example is made of raw materials of the following weights: 8 kg of copper-niobium alloy and 5 kg of praseodymium-copper alloy.

[0063] Example

[0064] Example 1

[0065] The high coercivity NdFeB magnetic material of this embodiment includes a magnetic material body and a coating attached to the surface of the magnetic material body, the coating includes a heavy rare earth layer located on the surface of the magnetic material body and a light rare earth layer located on the opposite side of the magnetic material body, the magnetic material body is made from the raw material of Preparation Example 1, the heavy rare earth layer is made from the heavy rare earth slurry of Preparation Example 6, and the light rare earth layer is made from the light rare earth slurry of Preparation Example 8. The ratio of the thickness of the heavy rare earth layer to the thickness of the magnetic material body is 1:5, and the ratio of the thickness of the light rare earth layer to the thickness of the magnetic material body is 4:5.

[0066] The preparation method of the high coercive force NdFeB magnetic material of the present embodiment comprises: (1) preparation of the magnetic material body, comprising the following steps: S1, melting and stripping: the above raw materials are melted and stripped to obtain stripped sheets; S2, hydrogen crushing and grinding: the stripped sheets obtained in step S1 are subjected to hydrogen crushing and air flow grinding to obtain hydrogen crushing powder; the particle size of the hydrogen crushing powder is 5 μm; S3, pressing and molding: the hydrogen crushing powder obtained in step S2 is pressed and shaped and oriented to obtain a raw magnet; wherein the density of the raw magnet is 4 g / cm 3 ; S4, magnetic material body: sinter the raw magnet of step S3 at 1100° C. for 5 h in a nitrogen atmosphere to obtain a magnetic material body 1;

[0067] (2) Preparation of a heavy rare earth layer, comprising the following steps: A1, slicing: cutting the magnetic material body obtained in step (1) into thin slices, the size of the slices being 6 mm×6 mm×6 mm; placing the slices in an ultrasonic water tank for ultrasonic washing to remove loose particles and impurities on the surface, and then taking them out and drying them with a hair dryer; A2, mixing: mixing dysprosium trifluoride, dysprosium nitride, dysprosium-nickel alloy, and carbon particles to form a mixed powder, placing the mixed powder in a vapor deposition furnace, and placing the slices on a mounting rack in the vapor deposition furnace, and continuously evacuating the vapor deposition furnace, and starting vapor deposition after evacuating the vacuum for 1 hour , firstly, the temperature of the evaporation furnace is raised to 550℃, kept at this temperature for 2h, then the temperature of the evaporation furnace is raised to 2200℃, kept at this temperature for 4h, and after cooling, a thin film is uniformly formed on one side of the slice in step A1 to obtain a thin film slice; A3, infiltration treatment: the thin film slice obtained in step A2 is infiltrated to obtain a treated slice; wherein, the infiltration treatment time is 5h; the infiltration treatment temperature is 1000℃; A4, heat treatment: the treated slice obtained in step A3 is surface quenched in a surface induction heating furnace, and tempered at 200℃ after quenching to obtain the second magnetic material body;

[0068] (3) Preparation of light rare earth layer, comprising the following steps: B1, preparation of light rare earth alloy sheet: using a rapid solidification process to melt copper-niobium alloy and praseodymium-copper alloy, and pouring them onto a copper roller to obtain a cast sheet, the melting temperature is 1350°C, the pouring temperature is 1300°C, and the cast sheet is cut into a size of the slice size in step A1, so as to obtain a light rare earth alloy sheet; B2, preparation of NdFeB magnet: attaching the light rare earth alloy sheet obtained in step B1 to the side of the second magnetic body opposite to the heavy rare earth layer, and performing a thermal diffusion treatment, the thermal diffusion treatment temperature is 800°C, the thermal treatment time is 12h, cooling to room temperature after the thermal diffusion treatment, and then performing a tempering treatment, the tempering treatment temperature is 600°C, and the tempering treatment time is 3h, so as to obtain.

[0069] Embodiment 2-5

[0070] Examples 2-5 are the raw material ratios of the magnetic material body, heavy rare earth layer, and light rare earth layer of high coercivity NdFeB magnetic materials. The raw material ratios of the magnetic material body, heavy rare earth layer, and light rare earth layer used in each example are shown in Table 1.

[0071] Table 1 Examples 1-5 are raw materials for each layer of high coercivity NdFeB magnetic materials

[0072]

[0073] The difference between Example 2-5 and Example 1 is that the raw material ratios of the magnetic material body, heavy rare earth layer and light rare earth layer of Example 2-5 are different, and the rest are exactly the same as Example 1.

[0074] The preparation method of the high coercive force NdFeB magnetic material of Examples 2-5 is exactly the same as that of Example 1.

[0075] Example 6

[0076] The difference between this embodiment and Embodiment 5 is that the ratio of the thickness of the heavy rare earth layer to the thickness of the magnetic material body is 2:6, the ratio of the thickness of the light rare earth layer to the thickness of the magnetic material body is 6:6, and the rest is exactly the same as Embodiment 5.

[0077] The preparation method of the high coercivity NdFeB magnetic material of this embodiment is exactly the same as that of Embodiment 5.

[0078] Example 7

[0079] The difference between this embodiment and Embodiment 5 is that the ratio of the thickness of the heavy rare earth layer to the thickness of the magnetic material body is 4:6, the ratio of the thickness of the light rare earth layer to the thickness of the magnetic material body is 6:6, and the rest is exactly the same as Embodiment 5.

[0080] The preparation method of the high coercivity NdFeB magnetic material of this embodiment is exactly the same as that of Embodiment 5.

[0081] Example 8

[0082] The high coercive force NdFeB magnetic material of this embodiment is exactly the same as that of Embodiment 6.

[0083] The preparation method of the high coercive force NdFeB magnetic material of this embodiment is different from that of Example 6 in that: Step S4 sinters the raw magnet obtained in Step S3, and the sintering temperature changes gradually. After vacuuming, the temperature is raised to 750°C at a heating rate of 5°C / min and kept warm for 30min; the temperature is raised to 1000°C at a heating rate of 5°C / min and kept warm for 20min; the temperature is raised to 1100°C at a heating rate of 2min and kept warm for 350min; the temperature is lowered to 1000°C at a cooling rate of 3°C / min, the temperature is lowered to 800°C at a cooling rate of 6°C / min; the temperature is lowered to 600°C at a cooling rate of 7°C / min, and the temperature is lowered to room temperature at a cooling rate of 15°C / min. The rest is exactly the same as Example 6.

[0084] Comparative Example

[0085] Comparative Example 1

[0086] The high coercive force NdFeB magnetic material of this comparative example includes a magnetic material body, and the magnetic material body is prepared by Preparation Example 1.

[0087] The preparation process of the high coercive force NdFeB magnetic material of this comparative example comprises the following steps: S1, melting and stripping: the raw materials are melted and stripped to obtain stripped sheets; S2, hydrogen crushing and grinding: the stripped sheets obtained in step S1 are subjected to hydrogen crushing and air flow grinding to obtain hydrogen crushed powder; the particle size of the hydrogen crushed powder is 5 μm; S3, pressing and molding: the hydrogen crushed powder obtained in step S2 is pressed and shaped and oriented to obtain a raw magnet; wherein the density of the raw magnet is 4 g / cm 3 ; S4, magnetic material body: sinter the raw magnet of step S3 at 1100°C for 5h in a nitrogen atmosphere to obtain.

[0088] Comparative Example 2

[0089] The high coercivity NdFeB magnet of this comparative example comprises a magnetic material body and a heavy rare earth layer attached to the surface of the magnetic material body, wherein the magnetic material body is prepared from the raw material of Preparation Example 1, and the heavy rare earth layer is prepared from the heavy rare earth slurry of Preparation Example 6. The ratio of the thickness of the heavy rare earth layer to the thickness of the magnetic material body is 5:5.

[0090] The preparation method of the high coercive force NdFeB magnetic material of the comparative example comprises: (1) preparation of the magnetic material body, comprising the following steps: S1, melting and stripping: the raw materials are melted and stripped to obtain stripped sheets; S2, hydrogen crushing and grinding: the stripped sheets obtained in step S1 are subjected to hydrogen crushing and air flow grinding to obtain hydrogen crushing powder; the particle size of the hydrogen crushing powder is 5 μm; S3, pressing and molding: the hydrogen crushing powder obtained in step S2 is pressed and shaped and oriented to obtain a raw magnet; wherein the density of the raw magnet is 4 g / cm 3 ; S4, magnetic material body: sinter the raw magnet of step S3 at 1100° C. for 5 h in a nitrogen atmosphere to obtain the magnetic material body;

[0091] (2) Preparation of a heavy rare earth layer, comprising the following steps: A1, slicing: slicing the magnetic material body obtained in step (1) into thin slices, the size of the slices being 6 mm×6 mm×6 mm; placing the slices in an ultrasonic water tank for ultrasonic washing to remove loose particles and impurities on the surface, and then taking them out and drying them with a hair dryer; A2, mixing: mixing dysprosium trifluoride, dysprosium nitride, dysprosium-nickel alloy, and carbon particles to form a mixed powder, placing the mixed powder in a vapor deposition furnace, and placing the slices on a mounting rack in the vapor deposition furnace, and continuously evacuating the vapor deposition furnace, and starting to evacuate the vacuum after 1 hour. Evaporation: first increase the temperature of the evaporation furnace to 550°C, keep it warm for 2 hours, then increase the temperature of the evaporation furnace to 2200°C, keep it warm for 4 hours, and after cooling, evenly form a thin film on one side of the slice obtained in step A1 to obtain a thin film slice; A3, infiltration treatment: subject the thin film slice obtained in step A2 to infiltration treatment to obtain a treated slice; wherein, the infiltration treatment time is 5 hours; the infiltration treatment temperature is 1000°C; A4, heat treatment: subject the treated slice obtained in step A3 to surface quenching in a surface induction heating furnace, and temper at 200°C after quenching to obtain.

[0092] Comparative Example 3

[0093] The high coercivity NdFeB magnetic material of this comparative example comprises a magnetic material body and a light rare earth layer attached to the surface of the magnetic material body, wherein the magnetic material body is prepared from the raw material of Preparation Example 1, and the light rare earth layer is prepared from the heavy rare earth slurry of Preparation Example 6. The ratio of the thickness of the light rare earth layer to the thickness of the magnetic material body is 5:5.

[0094] The preparation method of the high coercive force NdFeB magnetic material of the comparative example comprises: (1) preparation of the magnetic material body, comprising the following steps: S1, melting and stripping: the raw materials are melted and stripped to obtain stripped sheets; S2, hydrogen crushing and grinding: the stripped sheets obtained in step S1 are subjected to hydrogen crushing and air flow grinding to obtain hydrogen crushing powder; the particle size of the hydrogen crushing powder is 5 μm; S3, pressing and molding: the hydrogen crushing powder obtained in step S2 is pressed and shaped and oriented to obtain a raw magnet; wherein the density of the raw magnet is 4 g / cm 3; S4, magnetic material body: sinter the raw magnet of step S3 at 1100°C for 5h in a nitrogen atmosphere to obtain the magnetic material body, and cut the magnetic material body into thin slices with a size of 6mm×6mm×7mm; (2) Preparation of light rare earth layer, including the following steps: B1, preparation of light rare earth alloy sheet: melt copper-niobium alloy and praseodymium-copper alloy by rapid solidification process, and pour them onto copper rollers to obtain casting sheets, with the melting temperature of 1350°C and the pouring temperature of 1300 ℃, cut the cast sheet into the size of the slice size in step A1 to obtain a light rare earth alloy sheet; B2, preparation of NdFeB magnet: stick the light rare earth alloy sheet obtained in step B1 to the side of the magnetic material body opposite to the heavy rare earth layer, and perform thermal diffusion treatment at a temperature of 800℃ for 12h. After the thermal diffusion treatment, cool to room temperature, and then perform tempering at a temperature of 600℃ for 3h to obtain.

[0095] Detection Methods

[0096] Magnetic property test: High coercive force magnetic materials were prepared from Examples 1-8 and Comparative Examples 1-3. The properties of high coercive force NdFeB magnetic materials were tested according to the test method in GB / T3217-2013 "Magnetic Test Methods for Permanent Magnet (Hard Magnetic) Materials". The test results are shown in Table 2.

[0097] Table 2 Magnetic performance test of Examples 1-8 and Comparative Examples 1-3

[0098] Serial number Coercivity KOe Remanence Br / KGs Example 1 25.18 12.51 Example 2 25.15 12.48 Example 3 25.26 12.61 Example 4 25.29 12.63 Example 5 25.45 12.75 Example 6 25.98 12.81 Example 7 25.51 12.78 Example 8 26.21 12.95 Comparative Example 1 21.22 12.11 Comparative Example 2 23.15 12.31 Comparative Example 3 23.17 12.32

[0099] In combination with Example 1 and Comparative Examples 1-3, and in combination with Table 2, it can be seen that, relative to Comparative Examples 1-3, the present application attaches a heavy rare earth layer on the magnetic material body and attaches a light rare earth layer on the opposite side of the heavy rare earth layer, and the heavy rare earth elements such as dysprosium in the heavy rare earth layer are diffused into the crystal direction of the magnetic material body, and at the same time, a part of the neodymium on the surface of the magnetic material body is replaced, thereby increasing the coercive force of the magnetic material body. At the same time, the light rare earth elements in the light rare earth layer are diffused into the magnetic material body, thereby increasing the non-magnetic grain boundary phase and reducing the exchange coupling between the main phase grains, thereby increasing the coercive force of the magnetic material. In addition, the provision of the light rare earth layer facilitates reducing the preparation cost of the magnetic material while increasing the coercive force of the magnetic material.

[0100] In combination with Examples 1-3 and Table 2, it can be seen that the ratio of the raw material components of the magnetic material body is adjusted so that the ratio of the components of the magnetic material body is optimal, thereby improving the performance of the obtained magnetic material body, and thereby improving the coercive force and remanence of the obtained magnetic material.

[0101] Combining Examples 4-5 and Table 2, it can be seen that titanium and carbon are added to the components of the magnetic material body, and titanium and carbon cooperate with each other to form titanium carbide, thereby suppressing the size of the grains, thereby increasing the coercive force of the magnetic material body, and further increasing the coercive force of the magnetic material.

[0102] In combination with Examples 6-7 and Table 2, it can be seen that by adjusting the thickness of the heavy rare earth layer, it can be found that as the ratio of the thickness of the heavy rare earth layer to the thickness of the magnetic material body increases, the coercive force of the magnetic material first increases and then decreases. This is mainly because when the thickness of the heavy rare earth layer is too thick, the heavy rare earth in the heavy rare earth layer diffuses into the magnetic material body, so that the excess heavy rare earth forms an antiferromagnetic coupling with iron, thereby affecting the coercive force and remanence of the magnetic material.

[0103] It can be seen from Example 6 and Example 8 and Table 2 that in the process of preparing the magnetic material body, the sintering temperature of the raw magnet is optimized and a gradient sintering method is adopted, thereby facilitating improving the density of the magnetic material body and the coercive force of the magnetic material body.

[0104] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high coercivity NdFeB magnetic material, characterized in that: The invention comprises a magnetic material body and a coating attached to the surface of the magnetic material body, wherein the coating comprises a heavy rare earth layer located on the surface of the magnetic material body and a light rare earth layer located on the opposite side of the magnetic material body, wherein the magnetic material body is mainly made of the following raw materials in parts by weight: 70-80 parts of neodymium, 30-40 parts of gadolinium, 0.5-1 parts of copper, 30-35 parts of boron, 90-100 parts of cerium, 2-3 parts of aluminum, 1-5 parts of ferroniobium, and 350-370 parts of iron, and the heavy rare earth slurry of the heavy rare earth layer is mainly made of the following raw materials in parts by weight: 5-10 parts of dysprosium trifluoride, 2-3 parts of dysprosium nitride, 2-3 parts of dysprosium-nickel alloy, and 2-3 parts of iron; and the light rare earth slurry of the light rare earth layer is mainly made of the following raw materials in parts by weight: 5-8 parts of copper-niobium alloy and 3-5 parts of praseodymium-copper alloy. The ratio of the thickness of the heavy rare earth layer to the thickness of the magnetic material body is (1-2):(5-6); The ratio of the thickness of the light rare earth layer to the thickness of the magnetic material body is (4-6):(5-6); A method for preparing a high coercive force NdFeB magnetic material comprises: (1) Preparation of magnetic material body, including the following steps: S1, melting and stripping: melting and stripping the above raw materials to obtain stripping sheets; S2, hydrogen crushing and grinding: hydrogen crushing and air flow grinding of the stripping sheets obtained in step S1 to obtain hydrogen crushing powder; S3, pressing and molding: pressing and shaping the hydrogen crushing powder obtained in step S2 to obtain a green magnet; S4, magnetic material body: sintering the green magnet in step S3 to obtain a magnetic material body 1; The sintering temperature in step S4 changes in a gradient. After vacuuming, the temperature is increased to 750-850°C at a heating rate of 5-10°C / min, and the temperature is kept for 20-40min; the temperature is increased to 1000-1050°C at a heating rate of 3-5°C / min, and the temperature is kept for 10-30min; the temperature is increased to 1050-1100°C at a heating rate of 1-2min, and the temperature is kept for 300-350min; the temperature is reduced to 900-1000°C at a cooling rate of 3-4°C / min, the temperature is reduced to 700-800°C at a cooling rate of 5-7°C / min; the temperature is reduced to 600-700°C at a cooling rate of 6-8°C / min, and the temperature is reduced to room temperature at a cooling rate of 10-15°C / min; (2) Preparation of a heavy rare earth layer, comprising the following steps: A1, slicing: slicing the magnetic material body obtained in step (1) into thin slices; A2, mixing: mixing dysprosium trifluoride, dysprosium nitride, dysprosium-nickel alloy and iron to form a mixed powder, heating the mixed powder to melt and evaporate, and forming a thin film on one side of the slice obtained in step A1, thereby obtaining a thin film slice; A3, infiltration treatment: performing infiltration treatment on the thin film slice obtained in step A2, thereby obtaining a treated thin slice; A4, heat treatment: performing quenching and tempering treatment on the treated thin slice obtained in step A3, thereby obtaining a second magnetic material body; (3) Preparation of light rare earth layer, including the following steps: B1, preparation of light rare earth alloy sheet: using rapid solidification process to melt the raw materials and pour them onto a copper roller to obtain a cast sheet, that is, a light rare earth alloy sheet; B2, preparation of NdFeB magnet: attaching the light rare earth alloy sheet obtained in step B1 to the side of the second magnetic body opposite to the heavy rare earth layer, performing thermal diffusion treatment and tempering treatment, to obtain.

2. The high coercivity NdFeB magnetic material according to claim 1, characterized in that: The magnetic material body also includes 2-3 parts of titanium and 1-2 parts of carbon.

3. The high coercivity NdFeB magnetic material according to claim 1, characterized in that: Between the slicing in step A1 and the mixing in step A2, the slices are pre-treated and dried for later use. The pre-treatment is any one of alcohol wiping, electrostatic dust removal, and ultrasonic cleaning.

4. The high coercivity NdFeB magnetic material according to claim 1, characterized in that: The particle size of the hydrogen-broken powder in step S2 is 2-8 μm.

5. The high coercivity NdFeB magnetic material according to claim 1, characterized in that: The density of the raw magnet in step S3 is 2-5 g / cm 3 .

6. The high coercivity NdFeB magnetic material according to claim 1, characterized in that: In step A2, carbon particles are added to the mixed material.

Citation Information

Patent Citations

  • Method for preparing high-coercive force neodymium-iron-boron magnet through macroscopic non-uniform diffusion

    CN113808839A

  • Manufacturing method of rare-earth magnet

    JP2020136343A

Cited By

  • Grain boundary diffusion source for neodymium-iron-boron magnet, rare earth permanent magnet, preparation method and application

    CN120637079A